2009
DOI: 10.1016/j.neuroimage.2009.01.043
|View full text |Cite
|
Sign up to set email alerts
|

The neural basis of overall similarity and single-dimension sorting

Abstract: The ability to group stimuli into meaningful categories is fundamental to natural behavior. Raw perceptions would be useless without an ability to classify items as, for example, threat or food. Previous work suggests that people have a tendency to group stimuli either on the basis of a single dimension or by overall similarity (e.g., Milton, F.N., Longmore, C.A., and Wills, A.J. (2008). Processes of overall similarity sorting in free classification. J. Exp. Psychol. Hum. Percept. Perform, 34, 676–692.). It ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 63 publications
4
35
1
Order By: Relevance
“…Milton, Wills, and Hodgson (2009) reported greater frontal lobe activity in overall similarity classifiers than single-attribute classifiers, supporting the conclusion that overall similarity classification is more effortful. This conclusion is consistent with Combination Theory.…”
Section: Evidence For Combination Theorysupporting
confidence: 60%
See 1 more Smart Citation
“…Milton, Wills, and Hodgson (2009) reported greater frontal lobe activity in overall similarity classifiers than single-attribute classifiers, supporting the conclusion that overall similarity classification is more effortful. This conclusion is consistent with Combination Theory.…”
Section: Evidence For Combination Theorysupporting
confidence: 60%
“…Couchman, Coutinho & Smith, 2010;Goldstone & Barsalou, 1998). On the other hand, a series of more recent studies employing a slightly different procedure (Milton, Longmore & Wills, 2008;Milton, Wills & Hodgson, 2009;Wills, Milton, Longmore, Hester & Robinson, 2013b), largely support the opposite conclusion. The current investigation offers a reconciliation of these apparently incompatible studies.…”
Section: Introductionmentioning
confidence: 95%
“…This lack of a cerebellar tDCS effect on cognitive tasks could indicate that the cerebellum is not involved in cognition in general. This is, however, unlikely since several imaging studies (Nitsche et al, 2003; Blackwood et al, 2004; Hayter et al, 2007; Tomasi et al, 2007; Helie et al, 2010; Stoodley et al, 2012; Balsters et al, 2013; Lam et al, 2013; Davis et al, 2014; E et al, 2014) have shown cerebellar activity during cognitive tasks, including the task of categorization learning (Patalano et al, 2001; Milton et al, 2009). Anatomical evidence also supports the idea that the cerebellum is involved in fine-tuning processes in the prefrontal cortex (Kelly and Strick, 2003; Balsters et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Imaging studies have consistently shown cerebellar activation in various cognitive tasks (Nitsche et al, 2003; Blackwood et al, 2004; Hayter et al, 2007; Tomasi et al, 2007; Helie et al, 2010; Stoodley et al, 2012; Balsters et al, 2013; Lam et al, 2013; Davis et al, 2014; E et al, 2014) including categorization tasks (Patalano et al, 2001; Milton et al, 2009). On the other hand, inconsistent results have been found in patients with cognitive impairment due to cerebellar lesions.…”
Section: Introductionmentioning
confidence: 99%
“…Deception entails estimat ing the possible consequences of being caught, memo rizing information on previous actions, and choosing a strategy of further actions [31]. This increases the need for controlling the current activity (compared to the instructed truthful responses in the control trials), which is thought to be related to the so called fronto parietal system of cognitive control [32]. Hence, the activity detected in the frontal and parietal cortices may reflect the involvement of this system.…”
Section: Discussionmentioning
confidence: 99%